1992
DOI: 10.1111/j.1528-1157.1992.tb06222.x
|View full text |Cite
|
Sign up to set email alerts
|

Seizure Disorders: The Changes With Age

Abstract: Summary: Age has a profound influence on our approach to the convulsive disorders. Age is a variable which is an important determinant for risk factors for epilepsy. Age, as a surrogate of brain maturation, is a determinant of the specific characteristics of the seizure disorder in those with epilepsy, and age‐related changes in these manifestations can be identified. Age is a determinant for the occurrence of acute symptomatic seizures in several types of metabolic or central nervous system insults. Age is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
172
3
28

Year Published

1997
1997
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 338 publications
(210 citation statements)
references
References 29 publications
(10 reference statements)
5
172
3
28
Order By: Relevance
“…Recent studies in the United States and Europe indicate that the agespecific incidence of epilepsy is higher in those over the age of 65 years than in those in the first decade of life (Tallis et al, 1991;Hauser, 1992;DeLorenzo et al, 1997;Treiman et al, 1998;Wallace et al, 1998; Epilepsy Foundation of America, 1999).…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies in the United States and Europe indicate that the agespecific incidence of epilepsy is higher in those over the age of 65 years than in those in the first decade of life (Tallis et al, 1991;Hauser, 1992;DeLorenzo et al, 1997;Treiman et al, 1998;Wallace et al, 1998; Epilepsy Foundation of America, 1999).…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
“…Case studies suggest that aging alone may have an epileptogenic effect on the neuron and descriptive case studies and results from animal studies have suggested that advancing age increases the vulnerability to both seizure induction and acute neurological events for partial epilepsy and possibly for generalized-onset epilepsy, as well (reviewed in Wozniak et al, 1991;Hauser, 1992;Kerr et al, 2002). However, while it has been suggested that old age is the most common time for people to develop seizures (Hauser, 1992;Wallace et al, 1998), little is known about whether aging per se is an independent risk factor for epileptogenesis. Likewise, while epilepsy is one of the most common neurological conditions, our understanding of the molecular pathways that regulate cell death after seizure activity remain in their infancy and largely lag behind work in other areas of brain injury.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…This is very important because caloric restriction can be used in the therapeutics of diseases associated with the decrease of neuropeptide levels, such as epilepsy (Azarbar et al 2010;Hartman and Stafstrom 2013). It is known that aging brain is more susceptible to epileptic seizures (Hauser 1992;Hattiangady et al 2011) that was associated to the reduced levels of NPY and SS, neuropeptides known to have anticonvulsive properties (Baraban 2004;Stanley et al 2012). Indeed, it is known that caloric restriction reduces the epileptic seizures (Bough et al 1999;Azarbar et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…It affects 40% of the patients in adult series, and seizures arising from the mesial temporal lobe structures (i.e., amygdala and hippocampus) are the most common type (Babb and Brown, 1986;Hauser, 1992;Bertram, 2009). Several studies have demonstrated that mesial temporal sclerosis (MTS) is the most frequent histological finding in patients with mesial TLE (MTLE), and most of them suggested that cell loss and gliosis in specific subfields of the hippocampus were the most distinctive histological feature (Feuerstein and Hertting, 1986;Andrade and Nicoll, 1987).…”
Section: Introductionmentioning
confidence: 99%